ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN DI KLINIK PRATAMA BSMI KLATEN - Muhammad Khulaimi; Ari Andriyas Puji; Winda Nur Cahyo (Jurnal Surya Teknika, 2021)
Clinic is a health service facility that organizes individual health services that provide basic and specialized medical services, is organized by more than one type of health worker and is led by a medical staff (Menkes RI, 2001). Clinic Pratama BSMI Klaten is an institution engaged in the field of health services that provides quality basic health services. Present as a follow-up to the post-earthquake service process in Yogayakarta-Central Java on May 26, 2006 Inaugurated on November 13, 2006 by the Chairperson of the MPR. RI Dr. Hidayat Nurwahid, MA and the general chairman of BSMI DR.dr. H. Basuki Supartono, SP.OT, FICS, MARS. So far, the recording of patient medical records at the BSMI Klaten Primary Clinic is still using book media. This means that all these activities are carried out without the assistance of a computer so that it can result in lost or lost clinical records of various data. This, according to the author, is still very ineffective because it makes it difficult when presenting data such as an example of presenting data on treatment history or medical records for each patient which will take a long time. To overcome this problem, an information system that is able to provide fast information to patients and the public is needed. In order to improve services and improve the performance of each unit which is interconnected and integrated. Analysis and design of management information systems at the BSmi Klaten Pratama clinic which was made using the PHP programming language and the server using MySQL. The designed process consists of a registration unit, an initial examination of the patient by a nurse, a doctor's examination, a medical support unit, a pharmacy and a cash payment system, each of which can be data-integrated in a Clinical Management information system.